Hydrological and environmental issues of interbasin water transfers in India: a case of the Krishna River Basin - Smakhtin, Vladimir U.; Gamage, M.S.D.Nilantha; Bharati, Luna (International Water Management Institute, 2007)
This study attempts to examine those unique aspects of interbasin water transfer planning, which are of critical importance to the sustainable water resources development in India. It focuses on the crucial aspect of accurate quantification of surface water availability, which determines the entire feasibility of a water transfer. It also illustrates the impacts of upstream water resources development on the deltas' environment thus justifying the deltas' environmental flow requirements. The report targets government departments, research institutions and NGOs - primarily in India and other countries of the region - which are engaged or interested in issues of interbasin water transfer and environmental water management. The research intends to: contribute to the effectiveness of water resources planning and management in India; emphasize the need for urgent improvement of access to hydrometeorological data in the country; and aim to stimulate further debate on water transfers.